Post-vaccination anti-HBs testing among healthcare workers: More economical than post-exposure management for Hepatitis B - Camila Lucas de Souza; Thaís de Arvelos Salgado; Tatiana Luciano Sardeiro; Hélio Galdino Junior; Alexander Itria; Anaclara Ferreira Veiga Tipple (Universidade de São Paulo, 2020)
Objective: to compare the direct cost, from the perspective of the Unified Health System, of assessing the post-vaccination serological status with post-exposure management for hepatitis B among health care workers exposed to biological material. Method: cross-sectional study and cost-related, based on accident data recorded in the System of Information on Disease Notification between 2006 and 2016, where three post-exposure and one pre-exposure management scenarios were evaluated: A) accidents among vaccinated workers with positive and negative serological status tests for hepatitis B, exposed to known and unknown source-person; B) handling unvaccinated workers exposed to a known and unknown source-person; C) managing vaccinated workers and unknown serological status for hepatitis B and D) cost of the pre-exposure post-vaccination test. Accidents were assessed and the direct cost was calculated using the decision tree model. Results: scenarios where workers did not have protective titles after vaccination or were unaware of the serological status and were exposed to a positive or unknown source-person for hepatitis B. Conclusion: the direct cost of hepatitis B prophylaxis, including confirmation of serological status after vaccination would be more economical for the health system.